2012
DOI: 10.1142/s0218127412502148
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Vortices and Trajectories in Particle Diffraction

Abstract: We investigate the phenomenon of the diffraction of charged particles by thin material targets using the method of the de Broglie-Bohm quantum trajectories. The particle wave function can be modeled as a sum of two terms ψ = ψ ingoing + ψ outgoing . A thin separator exists between the domains of prevalence of the ingoing and outgoing wavefunction terms. The structure of the quantum-mechanical currents in the neighborhood of the separator implies the formation of an array of quantum vortices. The flow structure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 25 publications
2
14
0
3
Order By: Relevance
“…In a series of works published later on by Wisniacki and coworkers [282,283] it was shown that the origin of Bohmian chaos is in the evolution in time of those vortices. An analogous conclusion was also found by Efthymiopoulos and coworkers [197,[284][285][286][287], who showed that chaos is due to the presence of moving quantum vortices forming nodal point-X-point complexes. In particular, in reference [197] a theoretical analysis of the dependence of Lyapunov exponents of Bohmian trajectories on the size and speed of the quantum vortices is presented, which explains their earlier numerical findings [284,285].…”
Section: Role Of Vortical Dynamicssupporting
confidence: 81%
See 2 more Smart Citations
“…In a series of works published later on by Wisniacki and coworkers [282,283] it was shown that the origin of Bohmian chaos is in the evolution in time of those vortices. An analogous conclusion was also found by Efthymiopoulos and coworkers [197,[284][285][286][287], who showed that chaos is due to the presence of moving quantum vortices forming nodal point-X-point complexes. In particular, in reference [197] a theoretical analysis of the dependence of Lyapunov exponents of Bohmian trajectories on the size and speed of the quantum vortices is presented, which explains their earlier numerical findings [284,285].…”
Section: Role Of Vortical Dynamicssupporting
confidence: 81%
“…More recently and independently, Efthymiopoulos and coworkers have also tackled a similar issue by studying the diffraction of charged particles by thin material targets [197,198]. The exhaustive analysis presented by these authors is in agreement with the earlier findings by Hirschfelder and coworkers.…”
Section: Elastic Collisionssupporting
confidence: 76%
See 1 more Smart Citation
“…of ours [51], in which we implemented the de Broglie -Bohm approach in the case of electron diffraction through a thin crystal. In that study, however, we assumed a planar wave model for the propagation of the electron wavefunction in the longitudinal direction.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in the present paper we assume instead a finite longitudinal quantum coherence length. This assumption leads to a number of crucial new elements with respect to [51]. In fact, in order to achieve our goal we derive a wavefunction model by a refined implementation of basic scattering theory, so as to account for a fully-localized in space description of scattering.…”
Section: Introductionmentioning
confidence: 99%